2006
DOI: 10.1590/s0080-62342006000400011
|View full text |Cite
|
Sign up to set email alerts
|

Erros de medicação: tipos, fatores causais e providências tomadas em quatro hospitais brasileiros

Abstract: This study analyzed the causes, types, administrative measures taken and suggestions concerning medication errors according to the perspective of professionals involved with the medication systems in four Brazilian hospitals. It is an exploratory, survey-type, multicentric study. The sample consisted of professionals from the medical clinic and pharmacy in the above-mentioned hospitals. Semistructured interviews were used for data collection. Results showed that the most frequently error types mentioned by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
52

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 16 publications
(14 reference statements)
1
12
0
52
Order By: Relevance
“…Many studies report the incidence of adverse events in the practice of health care internationally (1,(9)(10)(11) . Even though the specificities of studies hinder comparison or replication in multiple contexts, all present similar conclusions related to the prevention of adverse events (9) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies report the incidence of adverse events in the practice of health care internationally (1,(9)(10)(11) . Even though the specificities of studies hinder comparison or replication in multiple contexts, all present similar conclusions related to the prevention of adverse events (9) .…”
Section: Discussionmentioning
confidence: 99%
“…However, studies concerning adverse events involving medication address many stages in this process and include in the results other actors such as pharmacists, physicians, pharmacy technicians, and others (14)(15) . The complexity that involves the medication process, from the writing of a prescription up to its administration, needs to be reviewed by healthcare workers because it is an activity exclusive to them, which requires precision, responsibility and scientific knowledge to avoid such adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…It may cause confusion, which goes against the Brazilian medical ethics code which establishes that the doctor is responsible for prescribing clearly and legibly and, therefore, without erasures 40 . Despite this, previous studies showed that erasures are common in Brazilian prescriptions 13,20,35 . Sometimes a 'free text' feature can be used to substitute erasures in prescriptions.…”
Section: Changes and Types Hospitalsmentioning
confidence: 94%
“…The discussion about medication errors in Brazil is still incipient and few articles have been published 1,2,12,13 . Medication errors accounted for 50% of adverse events detected in a study carried out in a private hospital in the city of Campinas (São Paulo State) 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Nessa perspectiva, a negligência, falhas individuais e problemas na administração de serviços constituem-se em importantes atributos das causas de erros, cometidos pelos profissionais de enfermagem, no que tange ao preparo e administração de medicamentos (20) .…”
Section: Considerações Finaisunclassified